2019
DOI: 10.1039/c9qm00089e
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional AIEgen with high cell-penetrating ability for intracellular fluorescence assays, imaging and drug delivery

Abstract: A diethylamino-modified multifunctional ESIPT AIEgen with superior cell-penetrating capacity is applied for intracellular fluorescence assays, imaging and drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Since DSS-4-DEA forms the aggregate it can thus be loaded with Cur. Therefore, the DSS-4-DEA displayed multiple bio applications [ 149 ]. Ma and group in the year 2019 designed a two-photon fluorescent molecule using DOX and conjugated polymer P(TPMA-co-AEMA)-PEI(DA)-Blink-PEG(PAEE Blink -DA) with an AIE-active property was synthesized.…”
Section: Aie Molecules For Drug Delivery Systemsmentioning
confidence: 99%
“…Since DSS-4-DEA forms the aggregate it can thus be loaded with Cur. Therefore, the DSS-4-DEA displayed multiple bio applications [ 149 ]. Ma and group in the year 2019 designed a two-photon fluorescent molecule using DOX and conjugated polymer P(TPMA-co-AEMA)-PEI(DA)-Blink-PEG(PAEE Blink -DA) with an AIE-active property was synthesized.…”
Section: Aie Molecules For Drug Delivery Systemsmentioning
confidence: 99%
“…Aggregation-induced emission (AIE) is an unusual photophysical phenomenon that some luminogens show no or weak fluorescence in solution but highly boosted emissions in the aggregate and solid state. Previous studies demonstrated that the cyano groups render acrylonitriles with twisted structures to result in AIE properties and avoid aggregation-caused quenching (ACQ) in the aggregate state in aqueous environment. , On the basis of acrylonitriles, many multicolor brightly emissive AIE luminogens (AIEgens) have been synthesized and applied in various fields such as fluorescence sensing and one- and two-photon bioimaging. Among these AIEgens, acrylonitriles with bright red emission are particularly preferred in bioimaging because of the reduced photodamage, minimal background autofluorescence, and deep tissue penetration. Unfortunately, highly red-emissive acrylonitrile-based AIEgens are still rare. In addition, their structures are complicated and their synthesis involves multistep reaction routes and time-consuming isolation or purification. On the other hand, for specific reactants, the change of reaction conditions generally exerts little effect on the reaction type to give only one main product.…”
Section: Introductionmentioning
confidence: 99%
“…A new class of fluorescent materials ( Figure 1B ) with aggregation-induced emission (AIE) discovered by Tang's group and others have received considerable attention due to their unique photophysical properties (Luo et al, 2001 ; An et al, 2002 , 2012 ; Shimizu et al, 2009 ; Shustova et al, 2013 ; Yan et al, 2015 ; Sasaki et al, 2016 ; Li and Li, 2017 ; Tsujimoto et al, 2017 ; Zhang et al, 2017 ; Ren et al, 2019 ; Guo et al, 2020 ; Hu et al, 2020 ; Kong et al, 2020 ; Mao et al, 2020 ; Qin et al, 2020 ). The widely accepted working mechanism of AIE-active fluorescent materials is restriction of intramolecular motions (Mei et al, 2015 ; Chen et al, 2019 ; Tu et al, 2020 ), thus the AIE materials generally show strong emission in aggregate and solid states and strong photobleaching resistance (Hong et al, 2011 ; Chen Y. et al, 2018 ; Cao et al, 2019 ; Li et al, 2019 ; Chen et al, 2020 ; Feng H. et al, 2020 ; He et al, 2020b ; Huang et al, 2020 ; Li Q. et al, 2020 ; Ni et al, 2020 ; Wei et al, 2020 ; Xu Y. et al, 2020 ; Yin et al, 2020 ). On the other hand, AIE materials mostly exist in the form of nanoaggregates in biological systems, which are not easily discharged by the biological system through metabolism, enabling long-term dynamic tracking (Xie et al, 2019 ; Niu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%